2018
DOI: 10.3892/ijo.2018.4485
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA‑MTO1 suppresses breast cancer cell viability and reverses monastrol resistance through regulating the TRAF4/Eg5 axis

Abstract: Circular RNAs (circRNAs), a class of endogenous RNAs, have emerged as an enigmatic class of genes. However, little is known about their value in the progression and chemoresistance of cancers. The present study sought to determine the expression profiles and potential modulatory role of circRNAs on breast cancer cell viability and monastrol resistance. Monastrol-resistant cell lines were established by exposing breast cancer cells to increasing concentrations of monastrol. A human circRNA microarray was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 42 publications
1
86
0
Order By: Relevance
“…For example, a previous in vitro study reports that circ‐MTO1/miR‐17/QKI‐5 regulatory circuit suppresses lung cancer cell proliferation . Furthermore, circ‐MTO1 inhibits cancer cell viability and reverses the resistance to monastrol in breast cancer cells . In this study, we found that circ‐MTO1 was downregulated in tumor tissue compared with non‐tumor tissue, which might be resulted from that circ‐MTO1 decreased malignant cell proliferation as shown in our in vitro experiments.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…For example, a previous in vitro study reports that circ‐MTO1/miR‐17/QKI‐5 regulatory circuit suppresses lung cancer cell proliferation . Furthermore, circ‐MTO1 inhibits cancer cell viability and reverses the resistance to monastrol in breast cancer cells . In this study, we found that circ‐MTO1 was downregulated in tumor tissue compared with non‐tumor tissue, which might be resulted from that circ‐MTO1 decreased malignant cell proliferation as shown in our in vitro experiments.…”
Section: Discussionsupporting
confidence: 75%
“…19 Furthermore, circ-MTO1 inhibits cancer cell viability and reverses the resistance to monastrol in breast cancer cells. 15 In this study, we found that circ-MTO1 was downregulated in tumor tissue provide some explanation to these results. b) Circ-MTO1 might also inhibit prostate cancer progression by repressing chemoresistance, which contributed to a better treatment response and subsequent favorable survival.…”
Section: Ta B L E 3 Analysis Of Factors Predicting Dfsmentioning
confidence: 54%
See 2 more Smart Citations
“…CircRNAs have been recognized as imperative regulators in multiple physiological/pathological processes. Although the exact roles of most circRNAs are still unclear, accumulating evidence has documented that some of them can function as oncogenic or tumor suppressive roles in human malignancies, including BC [7][8][9]. For example, Song et al revealed that silencing of circ_0007534 attenuates BC cell progression via affecting miR-593/MUC19 axis [10].…”
Section: Introductionmentioning
confidence: 99%